Bo and the merbaby - Elliott, Rebecca (2021)
Merbaby Flo was born with only one fin, unable to swim--so Bo and the other unicorns set out for the Shiny Sea to find the Golden Fish and ask Goldie to use his magic to help baby Flo.
Keywords: Unicorns -- Juvenile fiction; Mermaids -- Juvenile fiction; Magic -- Juvenile fiction; Helping behavior -- Juvenile fiction; Diaries -- Juvenile fiction; Unicorns -- Fiction; Mermaids -- Fiction; Magic -- Fiction; Helpfulness -- Fiction; People with disabilities -- Fiction; Diaries -- Fiction; Diary fiction